Taxation of Petroleum Products : Theory and Empirical Evidence - Gupta, Poonam; Mahler, Walter (Washington, D.C. : International Monetary Fund, 1994)
The domestic taxation of petroleum products is an important source of revenue in most countries. However, there is a wide variation of tax rates on petroleum products across countries, which cannot be explained by economic theory alone. This paper surveys different considerations advanced for taxing petroleum and presents petroleum tax rate data in 120 countries. It concludes that a significant reduction in the present extremely wide variation in petroleum prices and tax rates appears warranted.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet